Experience of Gender-based Violence by Internally Displaced Women in Southern Nigeria: A Cross-sectional Study. Issue 15 (August 2022) - Adejumo, Oluwadamilola A.; Ntoimo, Lorretta; Odimayo, Michael S.; Adebimpe, Wasiu O.; Okiei, Benedette; Osungbemiro, Walter; Olajuyigbe, Ebenezer; Igbafe, Kate; Temitayo-Oboh, Abiola; Faboya, Toyin; Oludiran, Olubunmi; Okonofua, Friday E.
Gender-based violence (GBV) is a reproductive health issue prevalent among persons in conflict and post-conflict situations, but is largely under-reported in Nigeria. Although GBV affects both sexes, the prevalence is higher in women as compared to men. The objective of this study was to assess the experiences of female internally displaced persons (IDPs) in Nigeria during conflict and post-conflict situations. The study was conducted among IDPs in Edo State, south-south region of Nigeria. Data were collected with a semi-structured questionnaire administered on 300 female IDPs. Descriptive and inferential analyses were conducted. GBV perpetrated by non-family members during conflict was experienced by 22.2% of the respondents while 13.5% experienced post-conflict violence. Up to 12.2% reported violence by intimate partners. Physical violence was commonly experienced during conflict, while sexual violence was most common post-conflict. Logistic regression analysis showed that the vulnerable categories of women were adolescents, unmarried women, women of Hausa origin, women who never attended school, and those whose displacement took place in the year prior to the study. The IDP camp appeared to offer some protection against GBV as those who had stayed in the camp longer were less likely to experience post-conflict GBV. The lack of implementation of effective laws and regulations that prevent violence against women and punish perpetuators in the country, and the ineffective security systems are some of the factors that sustain GBV. The results of this study have implications for the design of programs for the prevention of GBV during conflict and post-conflict situations.